Indoline alkaloids modulating the release of growth hormone by rat pituitary - T, SÃ©venet,; V, Jannica,; -Voegeleina, F, GuÃ©ritte; -Pajot, M.T, Bluet; C, Kordon, (Malaysian Journal of Science, 2000)
The general screening method and theory on rat pituitaries were briefly discussed. Active indoline alkaloids from Psychotria oleoides namely psycotridine, oleoidine and caledonine were found to stimulate the release of GH while hodgkinsine acted as antagonist to the SRIF receptor.